Newly professionalised physiotherapists: symbolic or substantive change?. Issue 2 (20th December 2019) - Anderson, Pauline; Warhurst, Chris
Abstract : Purpose: There is renewed interest in the professions as a range of occupations pursue professionalisation projects. The purpose of this paper is turn analysis to an important omission in current research – the skills deployed in the work of these professions. Such research is necessary because skills determine the formal classification of occupations as a profession. Design/methodology/approach: Drawing on qualitative research, this paper explores the deployment of skills in work of one newly professionalised occupation in the UK's National Health Service – physiotherapists. Findings: The findings point to a disconnect between how this occupation has become a profession (the skills to get the job, and related political manoeuvring by representative bodies) and the mixed outcomes for their skills deployment (the skills to do the job) in work as a profession. Originality/value: The paper provides missing empirical understanding of change for this new profession, and new conceptualisation of that change as both symbolic and substantive, with a "double hybridity" around occupational control and skill deployment for physiotherapists as a profession.